THE RELATIONSHIP BETWEEN ANEMIA AND ANXIETY DISORDERS AMONG ADOLESCENT GIRLS IN BEKASI DISTRICT, INDONESIA: A CROSS-SECTIONAL STUDY - Kinayungan, Utami Putri (Journal of Community Mental Health and Public Policy, 2025)
Background: Anxiety disorders are major mental health problem in Indonesia. In addition, the prevalence of anemia in adolescents is still high. Research shows that low iron levels can increase the risk of mental disorders, including anxiety disorders. Many studies have linked anemia to depressive symptoms, but research on anxiety disorders has not been widely studied. Purpose: to analyze the relationship between anemia and anxiety disorders in female adolescents. Methods: Quantitative research with a cross-sectional design conducted in three distinguished public schools in Bekasi Regency. The number of samples was 173 female adolescents selected using purposive random sampling techniques with inclusion criteria of being willing to provide blood samples, female students aged 15-18 years, and residing in Bekasi Regency. The exclusion criteria included students who were on a diet and consuming antidepressant medications. Anemia status was measured by Quick Check HB and anxiety disorders were assessed using the Depression Anxiety Scale (DASS 42) questionnaire. Results: Anemia in female adolescents was found to be 31.2%. Anxiety disorders were found to be 78.6%. The Bivariate test showed that there was no relationship between anemia status and depressive disorders (p-value = 0,167). Conclusion: There is no relationship between anemia status and depressive disorders in adolescents. Abstrak Background: Gangguan kecemasan menjadi masalah kesehatan mental utama di Indonesia. Selain itu, prevalensi risiko gangguan mental, termasuk gangguan kecemasan. Banyak studi yang mengkaitkan anemia dengan gejala depresi akan tetapi penelitian dengan gangguan kecemasan masih belum banyak diteliti. Tujuan: untuk menganalisis hubungan status anemia dengan gangguan kecemasan pada remaja. Metode: Penelitian kuantitatif dengan desain cross-sectional yang dilakukan di tiga sekolah unggulan di Kabupaten Bekasi. Jumlah sampel sebanyak 173 remaja putri yang dipilih dengan menggunakan teknik purposive random sampling dengan kriteria inklusi bersedia diambil darahnya, berusia 15-18 tahun, dan berdomisili di Kabupaten Bekasi. Kriteria eksklusi mengonsumsi obat antidepresan dan sedang menjalani diet. Status anemia diukur Quick Check HB dan ganguan kecemasan dinilai mengguunakan kuesioner Depression Anxiety Scale (DASS 42). Hasil: Remaja putri anemia ditemukan sebesar 31,2%. Gangguan kecemasan ditemukan sebesar 78,6%. Uji bivariant menunjukkan tidak ada hubungan anatara status anemia dengan gangguan depresi (p-value = 0,167). Kesimpulan: Tidak ada hubungan antara status anemia dengan gangguan depresi pada remaja. Perlu adanya studi lanjutan untuk melihat hubungan antara anemia dengan kecemasan.